Natural products for combating multidrug resistance in cancer - Ting Chen; Zhicheng Xiao; Xiaoyan Liu; Tingfang Wang; Yun Wang; Fei Ye; Juan Su; Xuan Yao; Liyan Xiong; Dong-Hua Yang (Elsevier, 2024)
Cancer cells frequently develop resistance to chemotherapeutic therapies and targeted drugs, which has been a significant challenge in cancer management. With the growing advances in technologies in isolation and identification of natural products, the potential of natural products in combating cancer multidrug resistance has received substantial attention. Importantly, natural products can impact multiple targets, which can be valuable in overcoming drug resistance from different perspectives. In the current review, we will describe the well-established mechanisms underlying multidrug resistance, and introduce natural products that could target these multidrug resistant mechanisms. Specifically, we will discuss natural compounds such as curcumin, resveratrol, baicalein, chrysin and more, and their potential roles in combating multidrug resistance. This review article aims to provide a systematic summary of recent advances of natural products in combating cancer drug resistance, and will provide rationales for novel drug discovery.